A case of improved hearing with cochlear implantation in Gaucher disease type 1. Issue 3 (June 2018) - Endo, Shiori; Mizuta, Kunihiro; Yamatodani, Takashi; Nakanishi, Hiroshi; Hosokawa, Kumiko; Misawa, Kiyoshi; Hosokawa, Seiji; Mineta, Hiroyuki
Abstract: Gaucher disease is a lysosomal storage disorder that is caused by congenital defective function of the enzyme glucocerebrosidase. Glucocerebroside that is not hydrolyzed by glucocerebrosidase mainly accumulates in the reticular tissue. We describe a Japanese boy with Gaucher disease type 1 who developed bilateral profound sensorineural hearing loss within approximately 4 years. We performed cochlear implantation initially on his right ear and again on his left ear 5 months later. The cochlear implants were successfully utilized with a speech discrimination score of 95% on a Japanese sentence recognition test. There are many reports of central hearing loss in Gaucher disease type 2 or 3. However, to the best of our knowledge, this is the first report of profound inner ear hearing loss with Gaucher disease. It also appears to be the first record of cochlear implantation for Gaucher disease. Cochlear implants may be useful for sensorineural hearing loss in patients with Gaucher disease without neurological symptoms other than hearing loss.